PENGEMBANGAN JENIS KOMODITI UNGGULAN KELAUTAN DAN PERIKANAN DI KABUPATEN KOLAKA - Muis Muis; Wa Ode Piliana (Jurnal Bisnis Perikanan (Journal of Fishery Business), 2016)
This study aims to determine (1) development of  the  types of superior commodity of marine and fisheries, (2) instrument in implementing economic development and the economic acceleration of coastal areas and  marine in Kolaka district. The sampling method used random sampling. The results of the analysis of fisheries of brackish water aquaculture, the types of superior commodity are vaname shrimp, windu shrimp and  milkfish. For fisheries of marine aquaculture, the kinds of superior commodity are seaweed, grouper and sea cucumbers. While for brackish water bargain, goldfish commodity becomes the superior followed by tilapia and catfish. Overview of the three commodity groups are based on several supporting aspects of a leading commodity: (1) Aspects of the availability of fish resources. (2) Aspects of productivity. (3) Aspects of market opportunities, three groups of fish resources, namely tuna and mackarel tuna, small pelagic and demersal/coral fish, the three groups can enter the market between regions. (4) Aspects of price, in terms of price per kilogram from the fishermen, demersal/coral fish especially reef fish, consumption which are marketed in the traders have greater sale value, followed by tuna and mackarel tuna, then small pelagic fish. (5). Aspect capital, fishing effort of a small pelagic fish and tuna more require huge capital. (6). Aspects of business systems, the marketing chain is not too long but it takes long time for transportation.Keywords : Coastal Areas, Superior Commodities, The Economy